2023
DOI: 10.5294/aqui.2023.23.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Burden and Perceived Social Support in Low-income Caregivers

Abstract: Objectives: To describe and correlate burden and social support in low-income caregivers of chronic patients. Material and methods: A descriptive and cross-sectional study was conducted with 170 low-income family caregivers of people with chronic diseases who answered a survey on sociodemographic and care variables, in addition to the Zarit scale to measure burden and the MOS questionnaire on perceived social support. The analysis was performed using descriptive and differential statistics. Results: Most careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, research conducted by De Fazio and others in southern Italy found that caregivers from lower socioeconomic backgrounds, with higher urban living conditions, and of older age, experience greater levels of burden and symptoms of depression [ 33 ]. Similarly, Chaparro-Díaz et al discovered that family caregivers with lower incomes need more social support to alleviate their burden [ 34 ]. In addition, we found that caregivers with higher education level had heavier care burden than those who with lower educational level.…”
Section: Discussionmentioning
confidence: 99%
“…However, research conducted by De Fazio and others in southern Italy found that caregivers from lower socioeconomic backgrounds, with higher urban living conditions, and of older age, experience greater levels of burden and symptoms of depression [ 33 ]. Similarly, Chaparro-Díaz et al discovered that family caregivers with lower incomes need more social support to alleviate their burden [ 34 ]. In addition, we found that caregivers with higher education level had heavier care burden than those who with lower educational level.…”
Section: Discussionmentioning
confidence: 99%